Silver mining in the Kingdom of Bohemia (13th-14th centuries) - Hrubý, Petr, 1973 červen 1.- (East Central and Eastern Europe in the Middle Ages, 1450-1450,, 2024)
In the 13th century, the monarchs of the Přemyslid dynasty, whose territory overlapped with that of the present-day Czech Republic, were increasingly affected by the dismal state of the Crown's finances. As a result, the Přemyslids initiated intensive silver exploitation, among other means to ensure income. This book's objective, based on interdisciplinary research, is therefore to describe and present the structure of mining and metallurgical areas in the kingdom of Bohemia, as well as to examine and identify how ore mining and metallurgy shaped and interacted with settlement organization and the medieval landscape.